PERANAN PENDIDIKAN AGAMA DALAM PEMBINAAN TINGKAH LAKU REMAJA - Esther Sitorus (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to review the role of Christian religious education in fostering adolescent behavior. The stages used in proving the real role of Christian religious education are face-to-face, student worship, pastoral counseling and catechism. The method used is descriptive research, which is deliberately designed to analyze and interpret data and determine the relationship or influence of independent variables on the dependent variable, then draw conclusions about the data collected and analyzed. The research location is in PTP IV Mandoge Private Junior High School. After all the data were analyzed, the researchers found that all accepted hypotheses had a value of 2.44 which means that there is a real role for Christian Religious Education through Face-to-face in Youth Behavior Development, a value of 2.47 which means that there is a real role between Christian Religious Education through Student Devotion in Youth Behavior Development, a value of 2.38 which means there is a real role between Christian Religious Education through Pastoral Counseling in Youth Behavior Development and a value of 2.40 which means that there is a real role between Christian Religious Education through Catechization in Behavioral Development Teen behavior. Keywords: Role, coaching, Christian religious education, adolescent behavior